PEMBELAJARAN KIMIA DENGAN MENGGUNAKAN TIPE TEAM GAMES TOURNAMENTS (TGT) DENGAN TEKNIK KARTU DAN TEKA TEKI SILANG (TTS) DITINJAU DARI INTERAKSI SOSIAL DAN KEMAMPUAN AWAL SISWA - Sitti Rohmi Djalilah (Universitas Hamzanwadi, 2012)
The purposes of the research were to know (1) the difference in students’ achievement between student who learnt using card and crossword puzzle techniques; (2) the difference in students’ achievement between students who had high and low social interaction; (3) the difference in students’ achievement between student who had high and low students’ prior knowledge; (4) the interaction between chemistry learning media and students’ social interaction towards student achievement; (5) the interaction between chemistry learning media and students’ prior knowledge towards student achievement; (6) the interaction between students’ social interaction and students’ prior knowledge towards student achievement; and (7) the interaction among chemistry learning media, students’ social interaction, and students’ prior knowledge towards student achievement. Experiment method used in this research. The population of the study was the tenth grade students of Madrasah Aliyah Mu’alimat NW Pancor in the academic year 2010/2011, consisting of eight classes . The sample was taken using cluster random sampling, consisted of two classes. The data was collected using test for student achievement and student prior knowledge, and questionnaire for student social interaction . The data analyses were performed by using Anova with 2x2x2 factorial design with α = 5%. The results of the study can be concluded that (1) the achievement of the students taught by the card technique of TGT was better than that of those taught by crossword puzzle technique; (2) the achievement of students’ high social interaction was better than that of students’ low social interaction; (3) the achievement of high students’ prior knowledge was better than that of low students’ prior knowledge; (4) there was no interaction between chemistry learning using TGT and students’ social interaction; (5) there was an interaction between chemistry learning using TGT interaction and students’ prior knowledge; (6) there was no interaction between students’ social interaction and students’ prior knowledge; and (7) there was no interaction among chemistry learning using TGT interaction, students’ social interaction, and students’ prior knowledge. Key words: Chemistry learning, TGT type, card technique, crossword /puzzle technique, social interaction, students’ prior knowledge, student achievement.